2021
DOI: 10.1007/s13555-021-00498-9
|View full text |Cite
|
Sign up to set email alerts
|

Italian Survey for the Evaluation of the Effects of Coronavirus Disease 2019 (COVID-19) Pandemic on Alopecia Areata Recurrence

Abstract: Introduction: The inflammation storm involved in coronavirus disease 2019 (COVID-19) infection and worsening and the psychological stress derived from current quarantine conditions can affect the course of many skin and scalp conditions. This study examined the possible effects of COVID-19 on alopecia areata (AA) relapse in patients suffering from these scalp conditions during the pandemic. Methods: The study was carried out in the form of an observational cross-sectional type using a questionnaire sent by mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 14 publications
2
24
0
2
Order By: Relevance
“…A South Korea-based previous study that examined the effect of underlying skin disease on COVID-19 susceptibility and mortality also detected no association between skin disease and COVID-19 (32). However, previous studies were mostly based on western society (3)(4)(5)(7)(8)(9), where the racial composition is different from South Korea. Also, the country where the research is based could derive different results.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A South Korea-based previous study that examined the effect of underlying skin disease on COVID-19 susceptibility and mortality also detected no association between skin disease and COVID-19 (32). However, previous studies were mostly based on western society (3)(4)(5)(7)(8)(9), where the racial composition is different from South Korea. Also, the country where the research is based could derive different results.…”
Section: Discussionmentioning
confidence: 97%
“…the way that COVID-19 itself affects autoimmune pathogenesis of AA (3)(4)(5) or that psychological stress caused by restriction policy against COVID-19 burdens AA (3)(4)(5)(6)(7)(8). However, there is a study that mild to moderate COVID-19 is not associated with worsening AA (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there is hardly any previous study on this issue from our country to compare with. However, during this virus outbreak, a number of studies conducted in different countries to explore the pandemic's stress-related hair diseases demonstrate a significant prevalence of hair diseases during this pandemic ( 18 , 37 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing cases of AA have been previously reported after the COVID-19 outbreak in Turkey [ 12 ]. Rinaldi et al [ 15 ] in a study of 389 patients with AA, in whom 34% had got infected with COVID-19, reported an increased relapse rate of AA among infected patients compared to the noninfected patients (44% vs. 12%). They considered higher rate of AA relapse in the COVID-19 pandemic to be related to the stress of quarantine and the inflammation induced by infection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%